2018
DOI: 10.1115/1.4041326
|View full text |Cite
|
Sign up to set email alerts
|

New Multiscale Approach for Machining Analysis of Natural Fiber ReinforcedBio-Composites

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. This is an author-deposited version published in: https://sam.ensam.eu Handle ID ABSTRACTNatural fibers are emerging in many industrial sectors to perform eco-friendly materials such as bio-composites. However, machining of natural fiber reinforced polymer (NFRP)composites remains a complex manufacturing process and the machinability of industrial components un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Indeed, the multiscale complex cellulosic structure of natural fibers prevents an efficient fiber shearing due to their high transverse elasticity which makes them highly sensitive to the variation of machining process parameters [10][11][12][13]. Furthermore, the multiscale random arrangement of the natural fibrous structure that includes the elementary fiber, the technical fiber, the fiber bundle, and the fibers yarn imposes the selection of the pertinent scale for analyzing the machined surfaces of NFRP composites [14]. The multiscale behavior is also present inside each elementary plant fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the multiscale complex cellulosic structure of natural fibers prevents an efficient fiber shearing due to their high transverse elasticity which makes them highly sensitive to the variation of machining process parameters [10][11][12][13]. Furthermore, the multiscale random arrangement of the natural fibrous structure that includes the elementary fiber, the technical fiber, the fiber bundle, and the fibers yarn imposes the selection of the pertinent scale for analyzing the machined surfaces of NFRP composites [14]. The multiscale behavior is also present inside each elementary plant fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical characterizations of the NFRCs were evaluated by the multiscale topographic of the milling surface signals. 133 The few representations of tool material and their geometry are summarized in Table 5 [134][135][136][137][138][139] which affects the performance of the composite.…”
Section: Millingmentioning
confidence: 99%
“…Due to the heterogeneous nature of composites the machining of composites is a complex process. 13 The existing literature has demonstrated that the machinability of composite materials is not the same as that of homogeneous materials. 14 Tool material and geometry have a large influence on damaged caused during machining composites.…”
Section: Introductionmentioning
confidence: 99%